Effects of dietary fat on muscle substrates, metabolism, and performance in athletes - Vogt, M.; Puntschart, A.; Howald, H.; Müller, B.; Mannhart, C.; Gfeller-Tuescher, L.; Mullis, P.; Hoppeler, H. (Medicine & Science in Sports & Exercise, 2003)
INTRODUCTION: The present investigation aimed at identifying differences in muscle structural composition, substrate selection, and performance capacity in highly trained endurance athletes as a consequence of consuming a high-fat or a low-fat diet. METHODS: Eleven duathletes ingested high-fat (53% fat; HF) or high-carbohydrate diets (17% fat; LF) for 5 wk in a randomized crossover design. RESULTS: In m. vastus lateralis, oxidative capacity estimated as volume of mitochondria per volume of muscle fiber (HF: 9.86 +/- 0.36 vs LF: 9.79 +/- 0.52%, mean +/- SE) was not different after the two diet periods. Intramyocellular lipid (IMCL) was significantly increased after HF compared with LF (1.54 +/- 0.27% vs 0.69 +/- 0.09%, P = 0.0076). Glycogen content was lower after HF than after LF, but this difference was not statistically significant (487.8 +/- 38.2 vs 534.4 +/- 32.6 mmol x kg-1 dry weight, P = 0.2454). Maximal power and [OV0312]O(2max) (63.6 +/- 0.9 vs 63.9 +/- 1.2 mL O(2) x min-1 x kg-1 on HF and LF) during an incremental exercise test to exhaustion were not different between the two diet periods. Total work output during a 20-min all-out time trial (298 +/- 6 vs 297 +/- 7 W) on a bicycle ergometer as well as half-marathon running time (80 min 12 s +/- 86 s vs 80 min 24 s +/- 82 s) were not different between HF and LF. Blood lactate concentrations and respiratory exchange ratios (RER) were significantly lower after HF than after LF at rest and during all submaximal exercise loads. CONCLUSIONS: Muscle glycogen stores were maintained after a 5-wk high-fat diet period whereas IMCL content was more than doubled. Endurance performance capacity was maintained at moderate to high-exercise intensities with a significantly larger contribution of lipids to total energy turnover.